A Super Permutation Algorithm - Dahal, Arogya; Khatiwada, Kalyan; Gautam, Siddhartha (International Journal of Scientific Research in Computer Science and Engineering, 2021)
We present an algorithm that finds a string that contains every permutation of n symbols as a contiguous sub string, also called super permutation, from a given starting permutation. The algorithm is simple and can be implemented for any element, as the algorithm is independent of the representation of n. The algorithm also produces shortest super permutation for n smaller than 6.